SATIRICAL APPROXIMATION USED IN ENGLISH LITERATURE (Conferencea, 2022)
Before attempting to emphasize the satirical method, it is necessary to accept some definitions regarding the nature of satire itself. Actually every writer, who deals with the subject of' satire, has own definition for the term satire. Edgar Johnson sums up the situation: “There wouldn't be much exaggeration in saying that everybody recognizes satire and that nobody knows what it is” [1; 3p].